Are tourism and energy consumption linked? Evidence from tourism dependent countries - Rasool, Harmain; Ul-Haq, Jabbar; Cheema, Ahmed Raza (Energy Economics Letters, 2023)
The tourism industry is one of the fastest-growing sectors across the globe. Tourism is not only playing a key role in the development of many small economies but is also considered a major source of income. Tourism-dependent economies are heavily reliant on the tourism sector. This study explored the relationships among energy consumption (EC), economic growth (EG), and tourism (TR) using panel data spanning 2000-2019, for tourism-dependent countries. Panel data methods like feasible generalized least-squares (FGLS) and panel corrected standard errors (PCSE) are employed for empirical analysis. Results reveal that the impact of EC on TR is mixed and sensitive to econometric techniques. While the impact of EG on TR is positive and robust to econometric techniques. We also used other control variables like total population and financial development. The impact of financial development and total population on TR is positive on tourism because they both boosted the tourism industry. Building on these findings, policy recommendations emphasize sustainable energy practices within the tourism industry. This study’s insights guide policymakers toward effective strategies that balance economic growth, energy efficiency and sustainable tourism development, ensuring the resilience of the tourism industry within evolving energy landscapes and economic dynamics.